Monkey wars - Kurti, Richard (New York : Delacorte Press, 2015)
When rhesus monkeys are brutally massacred on the streets of Kolkata by a troop of power hungry langur monkeys, a young langur soldier's life is changed forever.
Originally published in the United Kingdom by Walker in 2013.
Keywords: Rhesus monkey -- Fiction; Langurs -- Fiction; Monkeys -- Fiction; War -- Fiction; Rhesus monkey -- Juvenile fiction; Langurs -- Juvenile fiction; Monkeys -- Juvenile fiction; War stories; Young adult fiction